2006
DOI: 10.1016/j.icesjms.2005.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in abundance and catch composition of Cancer pagurus in Norwegian waters: biological reasoning and implications for assessment

Abstract: The edible crab (Cancer pagurus), which is abundant along the Norwegian coast north to Troms County, has been exploited in Norway since the start of the 20th century. The main fishery is in Mid-Norway and Helgeland (63°–67°N), which together land 75% of the Norwegian catch. The fishery is regulated by season, minimum legal size, and the discarding of soft or ovigerous females. Catches have never been systematically described, so this study presents data collected over 4 years by a reference fleet of profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 26 publications
2
38
0
2
Order By: Relevance
“…Crab stocks have also increased tremendously within the area of kelp recovery (H. Christie pers. obs., and information provided by local fishermen) as indicated by the annual landings of C. pagurus which have tripled in central Norway during the last decade (Woll et al 2006) The whelk Buccinum undatum was also observed interacting with the sea urchins during our tethering experiments. It is difficult to evaluate whether B. undatum exerts a genuine predation pressure on sea urchins or whether the observed interaction simply was an artifact of the puncture method and the tethering procedure.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Crab stocks have also increased tremendously within the area of kelp recovery (H. Christie pers. obs., and information provided by local fishermen) as indicated by the annual landings of C. pagurus which have tripled in central Norway during the last decade (Woll et al 2006) The whelk Buccinum undatum was also observed interacting with the sea urchins during our tethering experiments. It is difficult to evaluate whether B. undatum exerts a genuine predation pressure on sea urchins or whether the observed interaction simply was an artifact of the puncture method and the tethering procedure.…”
Section: Discussionmentioning
confidence: 62%
“…Climate change has great impact on species distributions, and the ongoing warming of the sea has proven to affect sea urchin−predator dynamics in both the northern and southern hemisphere (Ling & Johnson 2012, Clemente et al 2013). The range distribution of C. pagurus has recently expanded farther north in the NE Atlantic in correspondence with increasing ocean temperatures (Woll et al 2006, Brattegard 2011. Crab stocks have also increased tremendously within the area of kelp recovery (H. Christie pers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rising temperatures cause a decrease in physical disturbance by ice and a northward expansion and higher abundances of many boreal species (Weslawski et al 2011 and references therein). For example, benthic predatory crabs such as Cancer pagurus and H. araneus show increasing densities at the Norwegian and western Svalbard coast, respectively (Woll et al 2006;Berge et al 2009;Fagerli et al 2014). Due to higher consumer occurrence, we expect that new predator-prey interactions will develop in the future.…”
Section: Discussionmentioning
confidence: 99%